Wolbachia increase germ cell mitosis to enhance the fecundity of Laodelphax striatellus. (December 2020) - Guo, Yan; Khan, Jehangir; Zheng, Xiao-Ying; Wu, Yu
Abstract: Wolbachia are intracellular bacteria that infect a wide range of invertebrates and have evolved various strategies to alter host reproduction for their own survival and dissemination. In small brown planthopper Laodelphax striatellus, Wolbachia -infected females lay more eggs than uninfected females. Our previous study has shown that Wolbachia are abundant in ovarian cells of L. striatellus and change the number of apoptotic nurse cells in a caspase-dependent manner to provide nutrition for oogenesis. The cellular and molecular bases of the Wolbachia -mediated alterations in L. striatellus oogenesis remain largely unknown. Here, we investigated whether germ cell mitosis, which has been implicated in determination of egg production rates, influences the interaction between fecundity and Wolbachia in L. striatellus . We used an anti-phospho-histone 3 (pH3) antibody to label and visualize mitotic cells. Microscopic observations indicated that the Wolbachia strain w Stri increased the number of ovarioles that contained mitotic germ cells. The increased fecundity of Wolbachia -infected females was a result of mitosis of germ cells; the frequency of germ cell mitosis was much higher in infected females than in uninfected females. In addition, mitosis inhibition by Cdc20, CDK1, and CycB messenger RNA interference in Wolbachia -infected L. striatellus markedly decreased egg numbers. Live Wolbachia recolonization enhanced the egg production of uninfected L. striatellus by directly affecting mitosis regulators. Together, these data suggest that w Stri might increase germ cell mitosis to enhance the fecundity of L. striatellus in a mitosis-regulating manner. Our findings establish a link between Wolbachia -induced mitosis and Wolbachia -mediated egg production effects. Graphical abstract: Image 1 Highlights: Wolbachia increase the egg production of Laodelphax striatellus females regardless of the rearing temperature. The mitosis regulators might participate in Wolbachia -induced posterior germ cell mitosis in L. striatellus. 3. Knockdown of Cdc20, CDK1, and CycB in Wolbachia -infected females markedly decreases egg numbers. Live Wolbachia recolonization enhances the egg production of L. striatellus by directly affecting mitosis regulators.